Modelling Kinetics of the Boron-Oxygen Defect System. (August 2016) - Hallam, Brett; Abbott, Malcolm; Bilbao, Jose; Hamer, Phill; Gorman, Nicholas; Kim, Moonyong; Chen, Daniel; Hammerton, Katherine; Payne, David; Chan, Catherine; Nampalli, Nitin; Wenham, Stuart
Abstract: Here we report on modeling kinetics of the boron-oxygen defect system in crystalline silicon solar cells. The model, as supported by experimental data, highlights the importance of defect formation for mitigating carrier-induced degradation. The inability to rapidly and effectively passivate boron-oxygen defects is primarily due to the unavailability of the defects for passivation, rather than any "weakness" of the passivation reaction. The theoretical long-term stability of modules in the field is investigated as a worst-case scenario using typical meteorological year data and the System Advisor Model (SAM). With effective mounting of the modules, the modelling indicates that even in desert locations, destabilisation of the passivation is no concern within 40 years. We also incorporate the quadratic dependence of the defect formation rate on the total hole concentration, and highlight the influence of changing doping densities or changing illumination intensity on the CID mitigation process.